A STUDY TO PREDICT PATHOGENIC VARIANTS OF METTL5 GENE CAUSING INTELLECTUAL DISABILITY USING IN-SILICO ANALYSIS (Journal of Medical & Health Sciences Review, 2025)
The METTL5 gene encodes a methyltransferase enzyme crucial for the modification of ribosomal RNA (rRNA), a process essential for the proper functioning of ribosomes. Mutations in this gene have been associated with neurodevelopmental disorders such as microcephaly and intellectual disability, though the specific pathogenic variants remain poorly characterized. This study employed in silico analysis using various bioinformatics tools, including sequence alignment, structural modeling, and variant prediction algorithms, to identify and evaluate potentially harmful mutations in METTL5. Several rare and novel variants were identified, with one in particular, c.532G>A (p.Arg178His), located in a conserved region and consistently predicted to be pathogenic, suggesting it may impair methyltransferase function and disrupt rRNA modification. These findings highlight the utility of computational methods in predicting disease-causing genetic variants and lay the groundwork for future experimental validation, ultimately contributing to improved diagnosis and understanding of intellectual disabilities.